2009
DOI: 10.1111/j.0105-2896.2009.00859.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast‐like synoviocytes: key effector cells in rheumatoid arthritis

Abstract: SummaryRheumatoid arthritis (RA) remains a significant unmet medical need despite significant therapeutic advances. The pathogenesis of RA is complex and includes many cell types, including T cells, B cells, and macrophages. Fibroblast-like synoviocytes (FLS) in the synovial intimal lining also play a key role by producing cytokines that perpetuate inflammation and proteases that contribute to cartilage destruction. Rheumatoid FLS develop a unique aggressive phenotype that increases invasiveness into the extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
1,488
1
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 1,584 publications
(1,532 citation statements)
references
References 146 publications
(199 reference statements)
33
1,488
1
10
Order By: Relevance
“…25 Remarkably, uric acid crystals can induce various inflammatory mediators including cytokines, chemokines, proteases and reactive oxygen species, thereby playing an important role in the development of inflammatory responses. 26 Uric acid crystals have been shown to stimulate dendritic cell maturation, enhance antigenspecific immune responses and directly activate T cells.…”
Section: Discussionmentioning
confidence: 99%
“…25 Remarkably, uric acid crystals can induce various inflammatory mediators including cytokines, chemokines, proteases and reactive oxygen species, thereby playing an important role in the development of inflammatory responses. 26 Uric acid crystals have been shown to stimulate dendritic cell maturation, enhance antigenspecific immune responses and directly activate T cells.…”
Section: Discussionmentioning
confidence: 99%
“…1 Among the cells located in the inflamed joint, synovial fibroblasts are crucial players driving inflammation and bone erosion. 2 IL-34, 3 basically described as promoting monocyte proliferation and survival, and osteoclast differentiation, 4 is expressed by synovial fibroblasts of RA patients. Its expression, correlated with inflammation, the number of leucocytes and the severity of the synovitis, is upregulated by TNFα and IL-1β.…”
Section: Introductionmentioning
confidence: 99%
“…Effects of NOR on IL-1β-induced RANKL, PGE 2 , and MMP-13 expressions in FLS from AIA rats It has been demonstrated that proliferative FLS in the synovial membranes of RA-affected joints participates in both the propagation of inflammation and joint destruction, as they can produce large amounts of proinflammatory mediators and enzymes, including IL-1, IL-6, TNF-α, PGE 2 , and MMPs [20][21][22] .…”
Section: Resultsmentioning
confidence: 99%
“…The tumor-like proliferation of RA-FLS is considered to be one of the major effectors of cartilage and bone destruction in RA. They have the ability to produce massive amounts of pro-inflammatory [20][21][22]26] . Therefore, FLS cells were isolated from AIA rats and used in the following studies.…”
Section: Discussionmentioning
confidence: 99%